A comparative study of sulfate-reducing Desulfovibrio desulfuricans induced corrosion behaviors in Q235, X65, X70, and X80 pipeline steels. (February 2022) - Cai, Zheng; Xu, Jin; Wei, Boxin; Sun, Cheng
Abstract: The effects of sulfate-reducing bacteria (SRB) on the corrosion behaviors of Q235, X65, X70 and X80 pipeline steels in the soil environment of Shenyang were evaluated. Both the results of weight loss and electrochemical measurements showed that the corrosion rates of these steels decreased in the order of X70 > Q235 > X65 > X80. The corrosion rate from weight loss of X70 steel was 1.2 times as much as that for X80 steel during the 14-day of immersion. Pitting corrosion was observed on the surfaces of these steels. The maximum pit depth of X70 steel was 12.9 μm, which was 3.4 times that of X80 steel. It was also found that the Stern-Geary constants (B values) of different steels in the MIC system has a certain difference, which is less than the generally recognized B value under the active corrosion state 26 mV. Highlights: The MIC behaviors of Q235, X65, X70 and X80 steels were investigated. MIC rates of these steels decreased in the order of X70 > Q235 > X65 > X80. The Stern B values of these steels in the SRB environment has been discussed. The influence of microstructure on the corrosion behaviors was revealed.